Donkey milk as a non-bovine alternative: a review of its nutri-functional properties, applications, and challenges - Manan Preet Singh
Elevation in incidences of cow milk protein allergies warrants the need to investigate the suitability of non-bovine milk alternatives for human consumption. Donkey milk has emerged as a potential alternative attributed to its benefits to human health. Evidently, it is a great option for infants as it closely resembles human milk. Researchers have also investigated its suitability in producing numerous dairy products. This review discusses the various nutri-functional aspects of donkey milk, its applications and challenges in the manufacturing of infant formula, yogurt, cheese, ice cream, kefir, and fermented milk. Research updates on processing techniques (thermal and non-thermal) for donkey milk preservation are also delineated. Despite abundant nutrients and desirable functional properties, the growth of the donkey milk industry is not significant. This is due to the lower yield, scattered population, and lack of regulatory standards for both products and processing. Recommendation on research gaps and obstacles in its commercialization are also addressed.